The Legend Of The Indian Paintbrush - De Paola, Tomie (New York Putnam, 1988)
Little Gopher follows his destiny, as revealed in a Dream-Vision, of becoming an artist for his people and eventually is able to bring the colors of the sunset down to the earth.
AD840L
Keywords: Indians of North America -- Great Plains -- Legends; Artists